Serotype distribution and antimicrobial susceptibility of Streptococcus agalactiae isolates causing infections and asymptomatic colonization in Southwest Finland - Rahkonen, Roosa (My University, 2024)
Streptococcus agalactiae is a bacterium that may asymptomatically colonize the intestines and lower genital tract but can also cause infections in neonates and elderly people. Asymptomatic rectovaginal colonization of S. agalactiae during pregnancy can cause a risk for the neonate as the bacteria can be transmitted from mother to neonate during delivery. However, neonatal S. agalactiae infections can be efficiently prevented with screening and prophylactic antimicrobial treatment of pregnant women. Screening of pregnant women for S. agalactiae carriage at the late pregnancy is general practice in several countries, including Finland. Capsular polysaccharide (comprised of structural serotypes Ia, Ib, II–IX) is a virulence factor produced by S. agalactiae and the target of vaccines currently in development. This study aimed to determine the rate of S. agalactiae colonization in pregnant women in Southwest Finland. In addition, the aim is to compare the serotype distribution and antimicrobial susceptibility profile of colonizing and infectious S. agalactiae isolates. The colonizing isolates were collected from pregnant women during a clinical study. Isolates from invasive and urinary tract infections were obtained from Tyks Clinical microbiology unit. Altogether, 338 isolates were included in this study. Vaginal S. agalactiae colonization was detected in 14.2 % of pregnant women. The most common serotypes observed were Ia (28.1 %), V (22.2 %) and III (17.2 %). Serotype Ia was predominant among the colonizing (44.2 %) and UTI (32.3 %) isolates, whereas serotype V was most common in the invasive group (24.2 %). All isolates were susceptible to penicillin. Erythromycin resistance was observed in each group, but the resistance rate was highest among invasive isolates (34.4 %). This study provides valuable new information on the prevalence of vaginal S. agalactiae colonization in pregnant women and the serotype distribution of S. agalactiae in Finland. The observed rates of antimicrobial resistance emphasize the need for surveillance strategies.
Keywords: Streptococcus agalactiae, GBS, antimicrobial resistance, asymptomatic colonization, serotype